Growing without poverty: the role of good governance and pro-poor growth in the realisation of socio-economic rights and human development in Africa - Chenwi, Lilian (University of Pretoria, 2008)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2008.